Metode Pendidikan Sosial dalam QS. Ali Imran/3: 159 - Muhammad Hananika Anugerah Yusuf (Matan : Journal of Islam and Muslim Society, 2021)
Abstract: This research is a library research. The data has been collected through documentation method. The data were analyzed using the analytic interpretation method (tafsir tahlili) and presented descriptively. The results of the study indicated that qv. Ali Imran/3: 159 orders to be gracefull, be forgiving and democratic, tawakkal and the ideal attitudes in discussion. This verse give the solution to problems in social interactions. Qv. Ali Imran/3: 159 has an urgency in humans to interact with other people and the values of social education that can be used as a reference in social learning.